2013
DOI: 10.1016/j.brainres.2012.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Why trace and delay conditioning are sometimes (but not always) hippocampal dependent: A computational model

Abstract: A recurrent-network model provides a unified account of the hippocampal region in mediating the representation of temporal information in classical eyeblink conditioning. Much empirical research is consistent with a general conclusion that delay conditioning (in which the conditioned stimulus CS and unconditioned stimulus US overlap and co-terminate) is independent of the hippocampal system, while trace conditioning (in which the CS terminates before US onset) depends on the hippocampus. However, recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 144 publications
(191 reference statements)
0
13
1
Order By: Relevance
“…That is to say, by maintaining sustained activation during the trace interval, the PFC may support trace conditioning via working memory-like processes across the trace interval. These findings contrast with some theoretical accounts that suggest the hippocampus maintains a representation of the CS via recurrent loops during trace conditioning (Moustafa et al, 2013; Rodriguez & Levy, 2001). Interestingly, the mPFC, (PL and IL) is directly innervated by neurons originating in the VH (Hoover & Vertes, 2007) and these projections appear to be involved in modulating hippocampal-PFC theta coupling during working memory (O’Neill, Gordon, & Sigurdsson, 2013).…”
Section: Working Memory and Trace Conditioningcontrasting
confidence: 99%
“…That is to say, by maintaining sustained activation during the trace interval, the PFC may support trace conditioning via working memory-like processes across the trace interval. These findings contrast with some theoretical accounts that suggest the hippocampus maintains a representation of the CS via recurrent loops during trace conditioning (Moustafa et al, 2013; Rodriguez & Levy, 2001). Interestingly, the mPFC, (PL and IL) is directly innervated by neurons originating in the VH (Hoover & Vertes, 2007) and these projections appear to be involved in modulating hippocampal-PFC theta coupling during working memory (O’Neill, Gordon, & Sigurdsson, 2013).…”
Section: Working Memory and Trace Conditioningcontrasting
confidence: 99%
“…Studies have shown that lesions to the hippocampus disrupt trace fear learning (Bangasser et al, 2006; Burman et al , 2006; McEchron et al , 1998). Of note is a computational model accounting for hippocampal involvement in some forms of conditioning (Moustafa et al , 2013), although this model primarily accounts for the emergence of trace-cued responses over many more trials than those used in fear conditioning. The roles of different hippocampal subregions in this task are less clear with reports of conflicting roles for dorsal and ventral poles of the hippocampus (Cox et al, 2013; Czerniawski et al , 2009; Czerniawski et al , 2012; Esclassan et al , 2009b; Trivedi & Coover, 2006; Yoon & Otto, 2007).…”
Section: Neurobiology Of Trace Fear Conditioningmentioning
confidence: 99%
“…Various reports have demonstrated the role of the hippocampus in the formation of the temporal association between the CS and US in trace memory (Christian and Thompson, 2003). On the other hand, the CS-US association forms outside the hippocampus in delayappetitive-conditioning (Wallenstein et al, 1998;Rodriguez and Levy, 2001;Bangasser et al, 2006;Woodruff-Pak and Disterhoft, 2008;Moustafa et al, 2013). It has also been reported that only hippocampus-dependent tasks potentiate the neuronal proliferation and/or survival in the DG (Döbrössy et al, 2003;Deng et al, 2009Deng et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%